Tunable nonreciprocal transmission in nonlinear elastic wave metamaterial by initial stresses. (January 2020) - Li, Zhen-Ni; Wang, Yi-Ze; Wang, Yue-Sheng
Highlights: The effects of the initial stresses on the tunable propagation behavior in nonlinear phononic crystal and elastic wave metamaterial are presented. The influences of the initial stresses on both in-plane and anti-plane modes are discussed. The initial stresses can result in the movement to the low frequency regions of the central frequencies of the band gaps and the nonreciprocal zones. Abstract: In this investigation, the nonreciprocal transmission of elastic waves is achieved by the combination of asymmetric structure and nonlinear material. Our attention is focused on the effects of the initial stresses on the tunable propagation behavior in nonlinear phononic crystal and elastic wave metamaterial. Different components of the initial stresses are considered for both in-plane and anti-plane modes. Based on the Bloch's law and transfer/stiffness matrix method, the corresponding band structures and transmission coefficients of the generated fundamental and second harmonic waves are calculated and discussed. We find that the central frequencies of the band gaps and the nonreciprocal zones shift towards the low frequency regions as the initial stresses increase. This present work can be expected to provide a way to tune the transmission behaviors in nonlinear elastic wave metamaterial and mechanical diodes.